2017
DOI: 10.31901/24566586.2017/08.01.173
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of Conversational News Readers on Political and Economic Zimbabwe Online Media

Abstract: This paper aimed to discuss the perceptions held by employees towards the objectives of the system employed in their organization to assess their service interactions with customers, their perceptions of fairness of the system, and how such fairness relates to their satisfaction with the assessment outcomes. The study's population, consisting of employees working within service assurance call centres situated in Bloemfontein, Cape Town and Gauteng comprised of 117 respondents. To achieve the paper's objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The digital revolution also enabled citizen participation in social networking sites (SNSs) such as Twitter and Facebook. Social networking sites became alternative platforms for political deliberation, promoting freedom of expression and association in digital spheres (Banda 2010;Mathe 2017). The social networking sites Twitter and Facebook also played a vital role in Zimbabwe's 2018 elections where political organisations, non-governmental organisations (NGOs) like Pachedu, civil society organisations (CSOs), national and international election observers like the European Union (EU) and Zimbabwe Election Support Network (ZESN) mobilised voters for biometric voter registration (Mwonzora 2020).…”
Section: Elections and Information Technology In Zimbabwementioning
confidence: 99%
“…The digital revolution also enabled citizen participation in social networking sites (SNSs) such as Twitter and Facebook. Social networking sites became alternative platforms for political deliberation, promoting freedom of expression and association in digital spheres (Banda 2010;Mathe 2017). The social networking sites Twitter and Facebook also played a vital role in Zimbabwe's 2018 elections where political organisations, non-governmental organisations (NGOs) like Pachedu, civil society organisations (CSOs), national and international election observers like the European Union (EU) and Zimbabwe Election Support Network (ZESN) mobilised voters for biometric voter registration (Mwonzora 2020).…”
Section: Elections and Information Technology In Zimbabwementioning
confidence: 99%
“…The digital revolution also enabled citizen participation in social networking sites (SNSs) such as Twitter and Facebook. Social networking sites became alternative platforms for political deliberation, promoting freedom of expression and association in digital spheres (Banda 2010;Mathe 2017). The social networking sites Twitter and Facebook also played a vital role in Zimbabwe's 2018 elections where political organisations, non-governmental organisations (NGOs) like Pachedu, civil society organisations (CSOs), national and international election observers like the European Union (EU) and Zimbabwe Election Support Network (ZESN) mobilised voters for biometric voter registration (Mwonzora 2020) The paper argues that African polities should confront a more general problem, namely how to organise their governments.…”
Section: Elections and Information Technology In Zimbabwementioning
confidence: 99%
“…While a few studies have importantly identified possible connections between various forms of media and ethnic biases in several African countries (Mano, 2015; Mpofu, 2013; Nyamnjoh, 2010) so far, these have been limited to fairly isolated case studies, based on relatively small samples of data. More recently, scholars have begun to develop approaches that had previously only been implemented in more mature media markets, including systematic analysis of the use of ethnic and racial appeals in news and social media (e.g., Mathe, 2017). And Green (2018) provides a promising exploratory analysis of Google Trends data in the Nigerian context, demonstrating that for some ethnic groups, the number of searches of a group category is strongly correlated with state‐level group size 2 .…”
Section: Introductionmentioning
confidence: 99%